96-Well Plate-Based Method for Total Collagen Analysis of Cell Cultures. (May 2001) - Fenwick, S.A.; Curry, V.; Clements, S.; Hazleman, B.L.; Riley, G.P.
Total collagen assays are often laborious and use large quantities of consumables. We have developed a new method of assaying total 3 H-proline-labeled collagen from cultured cells. Cells and media are harvested from 96-well plates directly onto fiberglass filtermats and counted in the Wallac 1205 flat-bed scintillation counter (BetaPlate™). The assay was validated by comparison with a traditional total collagen assay. The resulting assay provides a rapid one-step method for quantifying collagen synthesis, which, unlike many collagen assays, does not require extensive dialysis or precipitation of proteins.